Roman expansion and integration of provincial territories: an interview with Vagner Carvalheiro Porto - Porto, Vagner Carvalheiro; Silva, Guilherme de Aquino (Romanitas - Revista de Estudos Grecolatinos, 2025)
Interview with Vagner Carvalheiro Porto, professor at the Museum of Archaeology and Ethnology of the University of São Paulo (MAE/USP). He holds a PhD (2007) and a Master’s degree (2001) in Archaeology from USP, and a Bachelor’s degree in History from the University of Santo Amaro (1994). He coordinates the Laboratory of Provincial Roman Archaeology (LARP/USP), where he conducts research on the Roman provinces of Syria-Palestine and the Iberian Peninsula. He also leads the research groups “Ancient Numismatics” and “Interactive Archaeology and Electronic Simulations” (ARISE). Additionally, he serves as co-editor-in-chief of the Revista do Museu de Arqueologia e Etnologia da USP and is a CNPq research productivity fellow. Among his most recent research projects are those carried out at the archaeological site of Tel Dor, in Israel. His work focuses on the analysis of Roman expansion and the integration of conquered territories into the imperial order.